Nanoscrolls: High‐Performance Photodiode Based on Atomically Thin WSe2/MoS2 Nanoscroll Integration (Small 30/2019). Issue 30 (26th July 2019) - Deng, Wenjie; You, Congya; Chen, Xiaoqing; Wang, Yi; Li, Yufo; Feng, Beibei; Shi, Ke; Chen, Yongfeng; Sun, Ling; Zhang, Yongzhe
Abstract : Nanoscrolls assembled by 2D materials are interesting and desirable in optoelectrical applications. A nanoscroll‐based heterostructure photodetector is reported by Yongzhe Zhang and co‐workers in article number1901544 . Moreover, it exhibits a well‐rounded performance, demonstrating its potential for future optoelectronics applications.